Gastric lactobezoar - Ultrasound diagnosis: A case report - Sharma, Bharat Bhushan; Sharma, Shashi; Bhardwaj, Naveen; Aziz, Mir Rizwan (Indian Journal of Child Health, 2016)
Gastric lactobezoars are found in neonates and diagnosed with the help of imaging modalities in the background of clinically presenting features.Inspissated milk mixes with the mucous and leads to ball like semisolid mass formation. The preterm infants are usually brought with abdominal swelling with or without features of intestinal obstruction. The condition is comparatively rare in children of higher age group. We present a 3-year-old male child who had a history of abdominal pain and swelling with occasional episodes of vomiting. Ultrasonography abdomen had shown some mass in stomach which was confirmed on subsequent barium and computerized tomography studies. He was fully recovered after the endoscopic conservative management with N-acetylcystein.The present case gains little more importance because of different age and sex group.